Pelatihan Dan Pembimbingan Penyusunan Laporan Keuangan Bumdes Bunga Bangsa Desa Ponteh Kabupaten Pamekasan - Alfazaki Ikbaar Hibatullah Lilik Nurul Almaidah; Deni Septiawan; Tiffany Dewi Attiqah Sari3; Alexander Anggono; Hanif Yusuf Seputro; Muhammad Asim ASy’ari; Mohammad Nizarul Alim; Tarjo (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
Ponteh Village area is one of the villages in Pamekasan Regency, in Ponteh Village there is a Village-Owned Enterprise (BUMDes) which is engaged in the trade sector by providing materials to help the surrounding community to grow crops. Basic accounting training and the preparation of BUMDes economic reviews are key to improving financial control capacity at the village level and to minimize the occurrence of errors in the preparation of financial statements. BUMDes as an economic entity managed with the help of village communities, plays an important role in local financial development. However, there is often a lack of knowledge and skills in terms of economic management and accounting. The research method uses a Service Learning approach. This service uses service learning because this service is collaborative between students and the community or BUMDes so that social change can be realized. This service activity has an impact on the BUMDes Bunga Bangsa management by giving a positive impression so that the Community Accounting Service runs smoothly and the BUMDes Bunga Bangsa management has understood the basic concepts and can increase their knowledge and skills in preparing financial reports.